Method of Community Leaders Informing Universal Humans in Kara Village Sampang District - Hoirul Anam; Akhmad Rifa’i (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The research conducted by the author aims to describe the social behavior of the Laok/Selatan hamlet community in their daily life. By using the theory of intercultural human formation. So that it can describe the purpose of the importance of an intercultural human formation for a country that has cultural pluralism, and can provide an overview of how to form a universal human/intercultural human, both national intercultural humans and international intercultural humans. Based on research conducted by this author. So the author can describe that the efforts made by K. Ahmad Subeiri informing universal human beings to the people of the Kara Laok/South hamlet include education, both formal education. Such as MI, SMPI, Diniyyah schools, which are included in competitions. As for non-formal education, it includes Muslimatan, recitation of the Koran, as well as recitation of the yellow books which is carried out on every school holiday such as the month of Ramadan, the Prophet's Birthday, and monthly recitation of material in the Koran. and Hadith, which discusses the beauty of Rosululloh's social relationships despite their differences in culture and beliefs, as well as verses of the Qur'an that explain human pluralism.